#TITLE_ALTERNATIVE# - YUSRIZAL (NIM 10103070), YOSEPH
A one dimensional analysis of drop formation in an ideal liquid jet is developed under the assumption that the axial velocity of the axisymmetric, remains independent of the radial coordinate. The resulting equations are then used for both linear and nonlinear studies. In the linear form, the model provides a stream stability relation that can be comparable to that of Rayleigh. For the nonlinear form, numerical simulations are carried out to study the satellite drop formation; with the present model, the satellite drop is always formed.